Single-dose Intramuscular Injection Toxicology of Danggui Pharmacopuncture (DGP) in Sprague-Dawley Rats - SeungHo Sun; JongJin Jeong; Sunju Park; KwangHo Lee; JunSang Yu; HyungSik Seo; KiRok Kwon (Korean Pharmacopuncture Institute, 2015)
Objectives: The purpose of the study is to assess both the approximate lethal dose and the single dose intramuscular injection toxicity of Danggui (Angelica gigantis radix) pharmacopuncture (DGP) in Sprague-Dawley (SD) rats. Methods: The experiments were conducted at the good laboratory practice (GLP) laboratory, Biotoxtech Co., which is a laboratory approved by the ministry of food and drug safety (MFDS). The study was performed according to the GLP regulation and the toxicity test guidelines of the MFDS (2009) after approval of the institutional animal care and use committee of Biotoxtech. Single doses of DGP were injected intramuscularly into the rats in three test groups of 6 week old SD rats (5 male and 5 female rats per groups) in the amounts of 0.1, 0.5, and 1.0 mL/animal for groups 2, 3, and 4, respectively, and normal saline solution in the amount of 1.0 mL/animal was injected intramuscularly into the rats (5 male and 5 female rats) in the control group. Observations of the general symptoms and weight measurements were performed during the 14 day observation period after the injection. Hematologic and serum biochemical examination, necropsy, and a local tolerance test at the injection site were done after the observation period. Results: No death was observed in three test groups (0.1, 0.5 and 1.0 mL/animal group). In addition, the injection of DGP had no effect on general symptoms, weights, hematologic and serum biochemical examination, and necropsy. The results from the local tolerance tests at injection site showed no treatment related effects in the SD rats. Conclusion: The results of single dose intramuscular injection of DGP suggest that the approximate lethal dose is above 1.0 mL/animal for both male and female SD rats and that intramuscular injection of DGP may be safe.